2009
DOI: 10.1038/aps.2009.169
|View full text |Cite
|
Sign up to set email alerts
|

Association between VDR and ESR1 gene polymorphisms with bone and obesity phenotypes in Chinese male nuclear families

Abstract: Aim: The goal of this study was to determine whether polymorphisms in the vitamin D receptor (VDR) and estrogen receptor alpha (ESR1) genes are associated with variations of peak bone mineral density (BMD) and obesity phenotypes in young Chinese men. Methods: A total of 1215 subjects from 400 Chinese nuclear families were genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and allele-specific multiple PCR (ASM-PCR) analysis at the ApaI, FokI, and CDX2 sites in the VDR gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 42 publications
3
40
1
Order By: Relevance
“…The TaqI, BsmI, FokI, ApaI, and other VDR polymorphisms have also been associated with obesity-related phenotypes in 6 additional studies conducted on Asian and European populations [33][34][35][36][37][38]. All reported associations for VDR SNPs are summarized in Table 1 and Table 2.…”
Section: Vdr Genetic Variantsmentioning
confidence: 99%
“…The TaqI, BsmI, FokI, ApaI, and other VDR polymorphisms have also been associated with obesity-related phenotypes in 6 additional studies conducted on Asian and European populations [33][34][35][36][37][38]. All reported associations for VDR SNPs are summarized in Table 1 and Table 2.…”
Section: Vdr Genetic Variantsmentioning
confidence: 99%
“…Although the mechanism of the underlying relationship between ESR RsaI and XbaI gene polymorphism and DF risk are not yet known, several studies have reported that Chinese women with the homozygous X genotype had higher BMD compared to those with the homozygous x genotype [38,39]. However, no significant associations were observed in studies of Korean or Chinese populations [40,41], and other opposite associations were also described in studies of Kurabayashi [42] and Zhang [43]. For the ESR RsaI polymorphism, no major effect on BMD was observed in studies of Arko [44] and Efstathiadou [45].…”
Section: Discussionmentioning
confidence: 97%
“…The coefficient of variability (CV) values were obtained from 15 volunteers with 3 measurements each. The respective CV values for the BMD of the lumbar spine 1-4, total hip, femoral neck, and trochanter were 1.39%, 0.70%, 2.22%, and 1.41% [1,[13][14][15] . The respective CV values for the fat mass measurements at the upper limbs, lower limbs, trunk, and total body were 7.58%, 3.28%, 2.52%, and 3.72%; the CV values for the lean mass at these sites were 1.18%, 1.59%, 1.12%, and 1.18%, respectively [15] .…”
Section: Subjectsmentioning
confidence: 94%
“…Using the female-offspring nuclear families, we not only detected an association between Myostatin polymorphisms and BMD variation, but we also successfully observed that genetic polymorphisms in estrogen receptor α and collagen1α2 likely influenced the attainment of peak BMD in Chinese females [1,18,20] . In addition, our latest study of genetic variants in the vitamin D receptor in relation to peak BMD in our male-offspring nuclear families detected an association [15] . In summary, the sample size of our maleoffspring nuclear families had sufficient power to detect a candidate gene as a QTL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation